Microduplications at the 15q11.2 BP1–BP2 locus are enriched in patients with anorexia nervosa. (June 2019) - Chang, Xiao; Qu, Huiqi; Liu, Yichuan; Glessner, Joseph; Hou, Cuiping; Wang, Fengxiang; Li, Jin; Sleiman, Patrick; Hakonarson, Hakon
Abstract: Microduplication at 15q11.2 have been reported in genetic association studies of schizophrenia and autism. Given the potential overlap in psychiatric symptoms of schizophrenia and autism with anorexia nervosa (AN), we were inspired to test the association of this CNV locus with the genetic susceptibility of AN using ParseCNV, a highly quality controlled CNV pipeline developed by our group. The CNV analysis was performed in 1017 AN cases and 7250 controls using the Illumina HumanHap610 SNP arrays data. We uncovered association of the 15q11.2 microduplication with AN with P = 0.00023, while no genetic association between the microdeletion of this region and AN was identified. Among four genes in this region that are not imprinted, NIPA1 has the highest expression in brain and encodes a magnesium transporter protein on early endosomes and the cell surface in neurons. Targeting at Mg 2+ uptake mediated by NIPA1 presents an interesting research topic for the explorations of novel therapy for AN and other neurobehavioral diseases, such as schizophrenia and autism. Highlights: Microduplication at 15q11.2 was analyzed in 1017 AN cases and 7250 controls. Association of the 15q11.2 microduplication with AN was identified with P = 0.00023. NIPA1 at this locus has the highest expression in brain and encodes a magnesium transporter protein.